3D reconstruction accuracy of two moving motion analysis systems: preliminary results - Bernardina, G. R. D.; Rodrigues, I. M.; Pinto, H. T.; Monnet, T.; Cerven, P.; Silvatti, A. P. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to compare the 3D reconstruction accuracy, through a rigid bar test, provided by two moving systems, optoelectronic cameras (MOCAP) and action sport cameras (ASC). The cameras were fixed in the same rolling rigid structure (4.4 × 4.0 × 2.5 m) and the data were acquired simultaneously by the two motion analysis systems. Algorithms were previously developed to perform the roto-translation of the global coordinate system from reference points arranged on the floor, while the cameras and the structure were moving (40 m, antero-posterior direction). The mean inter-markers distance was 598.93 mm and 585.27 mm, and the standard deviation was 6.20 mm and 2.23 mm, by ASC and MOCAP. Despite the ASC had a performance almost 3 times worse than the MOCAP, the ASC is a more portable system and less expensive.